2021
DOI: 10.1002/cncr.33611
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes of human papillomavirus–associated oropharynx carcinoma treated with surgery alone: A 12‐institution study of 344 patients

Abstract: Background The oncologic outcomes of surgery alone for patients with American Joint Committee on Cancer 7th edition (AJCC 7th) pN2a and pN2b human papillomavirus–associated oropharynx squamous cell carcinoma (HPV+OPSCC) are not clear. Methods The authors performed a 12‐institution retrospective study of 344 consecutive patients with HPV+OPSCC (AJCC 7th pT0‐3 N3 M0) treated with surgery alone with 6 months or more of follow‐up using univariate and multivariate analyses. Results The 2‐year outcomes for the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 54 publications
(72 reference statements)
2
19
0
1
Order By: Relevance
“…Our results, which confirm superior disease-free survival for p16-positive vs. p16-negative patients fall in line with multiple retrospective studies from recent years showing excellent disease control in HPV-positive patients after primary surgery-notably with patients undergoing un-adjusted treatment regimens, i.e. regular dose adjuvant therapy where warranted [1,15]. Preliminary results of deintensification trials for adjuvant treatment after primary surgery have been promising, however, deintensification was carefully adjusted to pathological results, for example excluding patients with high burden metastatic neck disease, extranodal extension or other potential risk factors which were determined by pathology [16].…”
Section: Discussionsupporting
confidence: 90%
“…Our results, which confirm superior disease-free survival for p16-positive vs. p16-negative patients fall in line with multiple retrospective studies from recent years showing excellent disease control in HPV-positive patients after primary surgery-notably with patients undergoing un-adjusted treatment regimens, i.e. regular dose adjuvant therapy where warranted [1,15]. Preliminary results of deintensification trials for adjuvant treatment after primary surgery have been promising, however, deintensification was carefully adjusted to pathological results, for example excluding patients with high burden metastatic neck disease, extranodal extension or other potential risk factors which were determined by pathology [16].…”
Section: Discussionsupporting
confidence: 90%
“…Although this period is relatively limited in duration, multiple studies have demonstrated short median times to local recurrence in surgically treated HPV+OPSCC ranging from 0.7 to 1.6 years. [1][2][3] In our study, no patient experienced local recurrence beyond 18 months of follow-up. While we noted in our study discussion that these patients remain at risk for recurrence, this study duration appears adequate to draw conclusions regarding local control in this patient population.…”
mentioning
confidence: 48%
“…Other studies have noted rates of lymphovascular invasion in single-modality surgical patients ranging from 13.4% to 18.2% and rates of perineural invasion ranging from 3.5% to 19.6%. 2,3 We agree that quality of life (QOL) remains a critical area of ongoing research in comparative study of treatment modalities but is beyond the scope of our study. The central impetus of avoiding adjuvant treatment in our patient population is precisely to improve long-term quality of life by minimizing adjuvant treatment sequelae while maintaining superior oncologic outcomes.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The goal of any surgical therapy for OPSCC is a complete resection of the tumor with adequate safety margins. This improves the overall prognosis of the patient, and the dose of adjuvant therapy administered depending on other risk factors can possibly be reduced [135]. HPV-positive OPSCC are particularly amenable to TORS because of their predominant localization in the tonsils or base of the tongue and their tendency towards lower T-stages at initial diagnosis compared with HPV-negative carcinomas [136].…”
Section: Surgery For Oropharyngeal Carcinomas: Tors Vs Open Resectionmentioning
confidence: 99%